Isolated Prolonged Activated Partial Thromboplastin Time and Contact Factor Deficiencies: Case Series and Management Review - Nisha Patel; Grace W. Conley; Laura A. McElroy; Majed A. Refaai (Research and Practice in Anesthesiology, 2016)
Background: Contact factor deficiencies are rare disorders that can cause grossly prolonged activated partial thromboplastin time (aPTT) and activated clotting time (ACT) while rarely affecting in vivo hemostasis. This in vitro laboratory phenomenon poses a particular challenge in surgical procedures that require anticoagulation monitoring. Case: Here we report two cases of contact factor deficiencies; a 67-year-old morbidly obese female with factor XII deficiency requiring revascularization of a graft and a 58-year-old female with prekallikrein (PK) deficiency undergoing routine muscle biopsy. Conclusion: Peri-operative anticoagulation monitoring poses a significant challenge in contact factor deficiency patients. Awareness of the challenges of contact factor deficiencies allows for optimal peri-operative management. Emerging literature supports that contact factors play a role in fibrinolysis. Increased surveillance of thrombotic events as well as avoidance of fibrinolytics may be necessary in these patients.